Comprehensive Creditworthiness Assessment of Rio Tinto - Shuang Zhou (Law and Economy, 2024)
This report examines Rio Tinto’s creditworthiness in relation to their request for an AU$1 million, three-year loan from the bank. In my capacity as the lending officer assigned to review this loan application, I will use four credit analysis techniques to determine the risks involved in giving the company credit and anticipate how to respond if business operations deteriorate or are unable to repay. A summary of the company’s financial situation, an analysis of its ability to repay debt, an appraisal of its business practices and industry prospects, and any relevant qualitative aspects influencing creditworthiness will all be included in the report. Informed choices about the loan application will be made through a thorough examination to minimize potential risks and guarantee the bank’s interests are protected.